Mycoplasma Pneumoniae bronchiolitis and hypoxemia: A retrospective cohort study on risk and prognosis - Yu Chen; Chenxi Lin; Rui Huang; Qi Chen; Min Zhang; XingQian Lai; QiaoRu Lin; Ling Chen (PLoS ONE, 2025)
Objective Mycoplasma pneumoniae (MP) bronchiolitis can potentially lead to severe respiratory symptoms and long-term complications. This study aimed to determine the risk factors for the development of hypoxemia in MP bronchiolitis and report its prognosis. Methods From January 2017 to December 2024, a total of 178 children with MP bronchiolitis, including 53 cases in the hypoxemia group and 125 cases in the control group, were selected. The clinical data, laboratory indicators, and imaging findings of the two groups were compared. Binary logistic regression analysis was used to identify the risk factors for the development of hypoxemia, and the receiver operating characteristic curve was employed to validate the predictive effect of the risk factors on hypoxemia. Results The hypoxemia group exhibited a higher incidence of a history of allergic diseases and wheezing sounds, accompanied by substantial elevations in C-reactive protein levels and greater areas of CT involvement ( P < 0.05). The presence of a history of allergic diseases, wheezing sounds, and the number of infected lung lobes were independent risk factors for the development of hypoxemia. The group with hypoxemia demonstrated a delayed improvement in symptoms, signs and lung function during follow-up ( P < 0.05). Seven cases of bronchiolitis obliterans were diagnosed in the hypoxemia group while none in the control group. Conclusion MP bronchiolitis patients with a history of allergic diseases, wheezing sounds, and involvement of at least three lung lobes are prone to developing hypoxemia. And those who experience hypoxemia recover more slowly during short-term follow-up and have a higher incidence of bronchiolitis obliterans.